STAT3 phosphorylation inhibition for treating inflammation and new bone formation in ankylosing spondylitis. (25th November 2020) - Jo, Sungsin; Won, Eun Jeong; Kim, Moon-Ju; Lee, Yu Jeong; Jin, So-Hee; Park, Pu-Reum; Song, Ho-Chun; Kim, Jahae; Choi, Yoo-Duk; Kim, Ji-Young; Shim, Seung Cheol; Choi, Sung Hoon; et al.
Abstract: Objective: AS is a rheumatic disease characterized by chronic inflammation and bony ankylosis. This study was to evaluate whether a signal transducer and activator of transcription 3 phosphorylation inhibitor (stat3-p Inh) could treat both chronic inflammation and bone formation in AS. Methods: Primary AS osteoprogenitor cells and spinal entheseal cells were examined for osteogenic differentiation. SF mononuclear cells (SFMCs) and lamina propria mononuclear cells (LPMCs) were obtained from AS patients. Inflammatory cytokine-producing cells were analysed using flow cytometry and ELISA. Female SKG mice were treated with stat3-p Inh, IL-17A blocker or vehicle. Inflammation and new bone formation were evaluated using immunohistochemistry, PET and micro-CT. Results: In the SKG mouse model, stat3-p Inh significantly suppressed arthritis, enthesitis, spondylitis and ileitis. In experiments culturing SFMCs and LPMCs, the frequencies of IFN-γ-, IL-17A- and TNF-α-producing cells were significantly decreased after stat3-p Inh treatment. When comparing current treatments for AS, stat3-p Inh showed a comparable suppression effect on osteogenesis to Janus kinase inhibitor or IL-17A blocker in AS-osteoprogenitor cells. Stat3-p Inh suppressed differentiation and mineralization of AS-osteoprogenitor cells and entheseal cells toward osteoblasts. Micro-CT analysis of hind paws revealed less new bone formation in stat3-p Inh-treated mice than vehicle-treated mice ( P  = 0.005). Hind paw and spinal new bone formation were similar between stat3-p Inh- and anti-IL-17A-treated SKG mice ( P  = 0.874 and P  = 0.117, respectively). Conclusion: Stat-3p inhibition is a promising treatment for both inflammation and new bone formation in AS.